COVID-19 and Precarious Employment: Consequences of the Evolving Crisis. (April 2021) - Matilla-Santander, Nuria; Ahonen, Emily; Albin, Maria; Baron, Sherry; Bolíbar, Mireia; Bosmans, Kim; Burström, Bo; Cuervo, Isabel; Davis, Letitia; Gunn, Virginia; Håkansta, Carin; Hemmingsson, Tomas; et al.
The world of work is facing an ongoing pandemic and an economic downturn with severe effects worldwide. Workers trapped in precarious employment (PE), both formal and informal, are among those most affected by the COVID-19 pandemic. Here we call attention to at least 5 critical ways that the consequences of the crisis among workers in PE will be felt globally: ( a ) PE will increase, ( b ) workers in PE will become more precarious, ( c ) workers in PE will face unemployment without being officially laid off, ( d ) workers in PE will be exposed to serious stressors and dramatic life changes that may lead to a rise in diseases of despair, and ( e ) PE might be a factor in deterring the control of or in generating new COVID-19 outbreaks. We conclude that what we really need is a new social contract, where the work of all workers is recognized and protected with adequate job contracts, employment security, and social protection in a new economy, both during and after the COVID-19 crisis.